Control of multi-level quadratic DC-DC boost converter for photovoltaic systems using type-2 fuzzy logic technique-based MPPT approaches - Souheyb Mohammed Belhadj; Bouziane Meliani; Habib Benbouhenni; Sarra Zaidi; Z.M.S. Elbarbary; Mohammed M. Alammer (Heliyon)
This paper introduces a type 2 fuzzy logic (T2FL)-based controller for maximum power point tracking (MPPT) in a high-gain three-level quadratic DC-DC boost converter (TLQDC-DCBC) designed for photovoltaic (PV) systems. High-gain DC-DC converters like the TLQDC-DCBC are beneficial in PV applications as they boost low PV voltages to higher levels, thereby reducing power losses and improving overall efficiency. The proposed MPPT-T2FLC addresses key limitations of traditional MPPT methods, including the oscillations near the maximum power point (MPP) in incremental conductance (IC) algorithms and the reduced precision of type-1 fuzzy logic (T1FL) controllers under uncertain environmental conditions. By incorporating type-reduction and interval type-2 fuzzy logic principles, the T2FLC enhances robustness, precision, and adaptability to rapidly changing irradiance and temperature levels. MATLAB simulations validate the superior performance of the proposed controller, demonstrating a consistent tracking efficiency of over 99.5 % across varying conditions (irradiance: 700–1000 W/m2, temperature: 25–45 °C). Comparative analysis reveals that the T2FLC improves tracking efficiency by up to 5.2 % compared to T1FLC and 7.5 % compared to IC, while also achieving faster convergence, reduced steady-state error, and enhanced stability. These results highlight the significant potential of the MPPT-T2FLC in optimizing energy extraction and improving the reliability of PV systems operating under dynamic environmental conditions.